Classification Profile of Swimmers with Physical Impairments in Turkey - Nazli Busra Cigercioglu; Sercan Yıllı; Büşra Kalkan Balak (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: The purpose of this study was to examine the classification profile of swimmers with physical disabilities in Turkey.Materials and Methods: In this cross-sectional study, 192 physically impaired swimmers (132 males, 60 females; mean age 20.8 ± 4.2 years) were evaluated. Athletes were classified according to the IPC functional classification system (S1–S10) based on standardized medical and technical assessments in line with World Para Swimming Classification Rules. Descriptive statistics and chi-square tests were performed.Results: The highest number of athletes was observed in class S9 (n=41), whereas the lowest was in S1 (n=2). Athletes were predominantly distributed in higher functional classes (S8–S10), indicating greater representation of swimmers with milder impairments. The most frequent eligible impairment criteria were muscle weakness (n=65), limb deficiency/dysmelia (n=49), and hypertonia (n=39), while no athletes were classified under ataxia or athetosis. Cerebral palsy and amputation were the most common health conditions. No significant association was found between classification level and sex (p=0.813) or professionalism level (p=0.979).Conclusion: Para swimming in Turkey is mainly represented by athletes with mild functional impairments, whereas those with severe impairments remain underrepresented. These findings provide the first national-level classification profile and may guide future policy planning and athlete development strategies.